Progression of chronic kidney disease in non- dialysis patients: a retrospective cohort - Jéssica Azevedo Aquino; Cláudia Lorenzo Oliveira; Alba Otoni; Cristina Sanches; João Victor Marques Guedes; Diego Bruno Morais; Thays Santos Mendonça; Flávio Augusto Morais; André Oliveira Baldoni (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract Evidence on factors associated with the progression of chronic kidney disease (CKD) is still under construction. The present study aimed to evaluate sociodemographic, clinical, and drug use factors associated with the progression of CKD. A retrospective cohort study was conducted with 193 patients with CKD stages 3A to 5- non-dialysis followed for three years in a Brazilian city. The outcome was the evolution to renal replacement therapy (RRT) or death. A total of 52.3 % (n = 101) were men and 83.4 % (n = 161) elderly. The median age was 72.0 years, and 22.3 % (n = 44) progressed to RRT or death, and the three-year mortality rate was 20.2 %. Participants exposed to angiotensin converting enzyme inhibitors or angiotensin II receptor blockers had a lower risk of progressing to the outcome (hazard ratio (HR) 0.25; p = 0.003) and higher survival (p = 0.022) when compared to those not exposed to these drugs. Age (HR 1.06;) and use of omeprazole (HR 6.25; CI; p <0.01) and hydrochlorothiazide (HR 2.80; p = 0.028) increased the risks of RRT or death. The results highlight the importance of rational management of pharmacotherapy for patients with CKD.